Effectiveness and Safety of Acupuncture as an Adjunctive Therapy for Post-Stroke Depression: An Overview of Systematic Reviews - Liu X; Zhu F; Zhang JL; He ZX; Yin S; Wu RH; He YY; Zeng F (Neuropsychiatric Disease and Treatment)
Xuan Liu,1,* Fengya Zhu,2,* Juan li Zhang,1 Zhao-Xuan He,1 Shao Yin,3 Ruo-Han Wu,1 Yan-Yan He,1 Fang Zeng4 1Acupuncture and Tuina School, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, 611137, People’s Republic of China; 2Zigong First People’s Hospital, Zigong, People’s Republic of China; 3Chengdu University of Traditional Chinese Medicine, Chengdu City, Sichuan Province, CN 610000, People’s Republic of China; 4Acupuncture and Tuina School, Acupuncture and Brain Science Research Center, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, 611137, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Zeng, Acupuncture and Tuina School, Acupuncture and Brain Science Research Center, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, 611137, People’s Republic of China, Email zeng_fang@126.comBackground: Post-stroke depression (PSD) is a common and serious neuropsychiatric complication that requires effective treatment options. Acupuncture as an adjuvant therapy shows promise, though current systematic reviews exhibit significant discrepancies in effectiveness/safety evidence with insufficient methodological rigor.Purpose: To evaluate systematic reviews assessing acupuncture as an adjuvant therapy for PSD.Methods: Electronic searches were conducted across eight databases from their inception to March 2024. The main search terms include “acupuncture and moxibustion therapy”, “post-stroke depression” and “systematic evaluation”. All systematic reviews underwent rigorous methodological evaluation employing four complementary assessment tools: AMSTAR 2 for methodological quality, ROBIS for risk of bias, PRISMA 2020 for reporting standards, and GRADE for evidence grading. The consistency level between the two reviewers is evaluated using the k-index.Results: Ten systematic reviews evaluated acupuncture as an adjuvant therapy for PSD. Using the AMSTAR 2 tool, 9 SRs (90%) were rated with a “very low” confidence level. According to the ROBIS criteria, only 3 SRs (30%) showed a low risk of bias. Although the report is overall comprehensive according to the PRISMA 2020 guidelines, there are significant shortcomings in areas such as evidence quality assessment (2/10, 20%). Employing the GRADE approach, 58.8% (20/34) as “very low”. The reliability among evaluators is satisfactory. Acupuncture as an adjuvant therapy combined with conventional treatments significantly improved HAMD/NIHSS scores versus monotherapy.Conclusion: While acupuncture as an adjuvant therapy seems to offer benefits in improving depressive symptoms and daily functioning among PSD patients, the overall low methodological quality of current systematic reviews limits the strength of this conclusion. More rigorous and high-quality evidence is needed to confirm these findings.Systematic Review Registration: PROSPERO CRD 42024533181.Keywords: post stroke depression, acupuncture, overview, systematic review, meta analysis